2020
DOI: 10.1371/journal.pntd.0008238
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and phylogenetic analysis of Crimean-Congo Hemorrhagic Fever viruses circulating in Pakistan during 2019

Abstract: Being an endemic country for Crimean Congo hemorrhagic fever (CCHF), this study aimed to explore the genetic diversity of CCHF virus (CCHFV) detected in Pakistan during 2019. Serum samples from patients with clinical signs of hemorrhagic fever attending tertiary care hospitals in Pakistan were tested for CCHFV RNA using real-time PCR at Department of Virology, National Institute of Health. The partial S-gene fragments were directly sequenced to determine the prevailing CCHFV genotypes and their molecular epide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 32 publications
4
22
0
Order By: Relevance
“…No mortality was observed in secondary cases (n = 8) with viral RNA copy number ranging from 10 6 −10 3 . The high CFR amongst CCHF cases observed in our study implies to the high viral load and bleeding [17,19,20,23,24,25]. Persistence of the CCHF viral RNA without any symptom or sign of active disease in survivors up to 76 th POD as noticed in our study has not been reported earlier.…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 57%
See 2 more Smart Citations
“…No mortality was observed in secondary cases (n = 8) with viral RNA copy number ranging from 10 6 −10 3 . The high CFR amongst CCHF cases observed in our study implies to the high viral load and bleeding [17,19,20,23,24,25]. Persistence of the CCHF viral RNA without any symptom or sign of active disease in survivors up to 76 th POD as noticed in our study has not been reported earlier.…”
Section: Plos Neglected Tropical Diseasessupporting
confidence: 57%
“…The 33 CCHFV sequences retrieved from the 29 clinical specimens and 4 tick pools were each belonging to L and S gene clustered with the Asian clade. The Asian clade is further grouped into Asia 1 and Asia 2 subgroups [19,20]. The sequences retrieved in this study were found in both the subgroups.…”
Section: Ngs and Phylogenetic Analysismentioning
confidence: 71%
See 1 more Smart Citation
“…Likewise, in a study conducted in Georgia, it was found that the disease was mostly found in farmers and people who lived in rural areas [14]. In a study investigating the molecular and clinical epidemiology of CCHF in Oman [15], the main risks of infection for contracting CCHF were animal contact (73%) and butchery (88%). When the distribution of ticks according to occupations was examined in the current study, it was found that 54.1% of the 362 patients were engaged in farming and animal husbandry, 38.1% were from other occupational groups, 3.9% were students, 3.6% were children, and 0.3% were health personnel.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with S and L fragments, the rearrangement of the M fragment is more frequent (Deyde et al, 2006). According to phylogenetic analysis, CCHFV can be divided into seven genetic categories related to geographic origin: two from Asia, two from Europe, and three from Africa (Umair et al, 2020).…”
Section: Introductionmentioning
confidence: 99%